1989
DOI: 10.1002/1097-0142(19890301)63:5<881::aid-cncr2820630515>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Multiple carcinoids and endocrine cell micronests in type a gastritis. Their morphology, histogenesis, and natural history

Abstract: Six cases of type A gastritis associated with multiple carcinoids and/or endocrine cell micronests (ECM) in the atrophic fuindic mucosa were examined light microscopically, immunohistochemically, and ultrastructurally. The ECM and carcinoids were mainly composed of enterochromaffin-like (ECL) cells. The cells were hyperplastic only in the atrophic fundic glands and pseudopyloric glands, but not in the intestinal metaplastic gland. It is suggested that the development of both the ECM and the carcinoids is highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1
1

Year Published

1990
1990
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 19 publications
2
35
1
1
Order By: Relevance
“…Gastric carcinoid tumors are often found in patients diagnosed as having type A gastritis. In patients with type A gastritis, the development of carcinoids and the widespread hyperplasia of enterochromaffin-like cells are related to atrophic changes of the fundic mucosa and the trophic action of subsequently raised serum gastrin levels [2].…”
Section: Introductionmentioning
confidence: 61%
“…Gastric carcinoid tumors are often found in patients diagnosed as having type A gastritis. In patients with type A gastritis, the development of carcinoids and the widespread hyperplasia of enterochromaffin-like cells are related to atrophic changes of the fundic mucosa and the trophic action of subsequently raised serum gastrin levels [2].…”
Section: Introductionmentioning
confidence: 61%
“…This is consistent with our gastric ECC findings. However, it is reported that many gastric CD cases are formed by aggregations of endocrine cell micronests, predominantly composed of enterochromaffinlike cells, caused by the hypertrophic effect of hypergastrinemia, which is induced by extensive atrophic fundic gland mucosal change [18]. In the present study we could not find a CD case associated with the adenocarcinoma component, which presents little evidence for adenocarcinoma precursor cell-derived CD.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the ECM which spread around the carcinoid in the resected specimen do not cause malignant transformation. Considering these facts, ECM can (12).…”
Section: Several Kinds Of Endocrine Cells Including Enterochromaffin mentioning
confidence: 78%